Rolando Villazón, one night in Berlin Südwestdeutsche Kammerphilharmonie Konstanz - Rossini, Gioacchino 1792-1868; Salvi, Matteo; Massenet, Jules 1842-1912; Verdi, Giuseppe 1813-1901; Massenet, Jules 1842-1912; Verdi, Giuseppe 1813-1901; Mascagni, Pietro 1863-1945; Cilèa, Francesco 1866-1950; Lehár, Franz 1870-1948; Sorozábal, Pablo 1897-1988 (Finkernagel & Lück, 2006)
In front of an excited audience in Berlin, a colourful recital by the Mexican tenor. Rolando Villazón is a tornado, however, he is a kindly tornado that destroys nothing on its path but spreads happiness. His fans are fortunate: the Mexican tenor is intent on giving his best to them, with a generosity resembling the quality of his voice full of sunshine. "What I'm looking for in a concert is the human experience. I want people to leave taking something inside along with them." The audience at the recital he gave in Berlin, in the Philharmonic concert hall, was very enthusiastic. In the film we see Villazón perform arias from the Bel Canto by Donizetti, Cilea and Mascagni. He also let himself be filmed (in his shower!) and interviewed backstage where we see him, like a caged lion, waiting for the second part of the performance. Few artists are as spontaneous and natural. "I wanted to perform ever since I was a small child. But the stage, for me, is also life. The instrument of a singer is his voice, his body, his being even." And he invests all of these fully